Lexicalização-degramaticalização do plural no português falado em Belo Horizonte - Maurício Rubens de Carvalho Guilherme (2021)
The present thesis has as its theme the erasure of the plural marks of the name in the portuguese spoken in Belo Horizonte. The purpose of this research is to investigate the structure of noun phrases (NP) that refer to pluralities, without, however, presenting suffixed plural markers in their nucleus, and, in some cases, nowhere in the NP. For this, a set of occurrences of this phenomenon was collected, through a standardized test of image description, in order to analyze both the linguistic and social contexts in which they occurred, as well as the causes that would be motivating this process by which the language would be passing. After the collected data, a quantitative analysis was carried out with the aid of statistical methods. When analyzing the presence of plural marks in the nucleus of the NP and its antecedent, the results revealed the occurrence of three structures: the conservative form, in which the plural mark is present both in the nucleus and in the antecedent, as in "as mãos" and the innovative forms, an in which there is no plural mark in the NP, called Null plural, as in "a mão", and another in which this mark is present only in the antecedent of the nucleus, called Non-redundant plural, as in "as mão". From a theoretical point of view, the conclusions reached are that the Null plural is the product of a Lexicalization (Cf. Gruber (1965), McCawley (1968), Talmy (1985, 2000) while the Non-redundant plural is the result of a process still in progress of degramticalization (Cf. Norde, 2011; Gonçalves, 2011)